Bird Extinctions in Brazil’s Atlantic Forest and How They Can Be Prevented - Develey, Pedro F.; Phalan, Benjamin T. (Frontiers in Ecology and Evolution, 2021)
Bird species extinctions in the Atlantic Forest of Brazil have been predicted since the early 1990s, but it has become accepted wisdom that none have yet been documented. We revisit this question in light of updates to the Red List, and conclude that between five and seven bird species have likely been driven to extinction in the wild in this biome in recent decades, plus a further two species that occurred elsewhere in Brazil. These extinctions were the result of habitat loss in combination with other threats. A further nine Atlantic Forest bird species are Critically Endangered, plus six from elsewhere in Brazil. We review growing efforts to help these species avoid extinction using a range of tools including multi-stakeholder planning, advocacy, habitat protection and restoration on public and private land, focused research, and ex situ methods, drawing on examples from the most threatened Atlantic Forest endemics. Conservation organisations, local communities, government agencies, zoos, international funders, universities and others are working together to prevent these species from disappearing. While the political environment in Brazil has rarely been more hostile to conservation, there are also some positive trends. Rates of deforestation in the Atlantic Forest have fallen, forest restoration and recovery is increasing, and an unprecedented number of ordinary people are taking an interest in birds and participating in citizen science. With dedication, collaboration, sufficient resources, and a focus on evidence-informed solutions, we are hopeful that many of the Critically Endangered species can be pulled back from the brink of extinction.